2001
DOI: 10.1103/physrevlett.86.1323
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Entry and Nucleation of Antivortices in a Mesoscopic Superconducting Triangle

Abstract: The nucleation of superconductivity in mesoscopic equilateral triangles is investigated by using the linearized Ginzburg-Landau equation (LGLE). The trigonal symmetry of the sample has a profound effect on the superconducting state in the presence of a magnetic field H leading, in particular, to the formation of antivortices in symmetry-consistent states. For the same given irreducible representation, vortices enter always by three via the middle of the edges, approach the center, and then are dispatched towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
94
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 20 publications
7
94
1
Order By: Relevance
“…Theoretical studies [14][15][16][17][18][19] showed that different types of vortex states can appear in such samples: giant vortex states, multivortex states, combinations of giant and multivortex states, and even states where vortices and antivortices coexist. 14 In addition, it became clear that the stability of the different vortex states strongly depends on the sample shape.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies [14][15][16][17][18][19] showed that different types of vortex states can appear in such samples: giant vortex states, multivortex states, combinations of giant and multivortex states, and even states where vortices and antivortices coexist. 14 In addition, it became clear that the stability of the different vortex states strongly depends on the sample shape.…”
Section: Introductionmentioning
confidence: 99%
“…For superconductors expectations are even more spectacular. In macroscopic type-II superconductors a triangular lattice of single flux quanta is formed, whereas two kinds of fundamentally new vortex states have theoretically been predicted in mesoscopic superconductors where the sample size approaches the size of Cooper-pairs [2,3,4,5]; (i) multivortex states (MVSs) with a unique spatial arrangement of singly quantized vortices, and (ii) multiply quantized or giant vortex states (GVSs) with a single core in the center [6,7].Although several experimental techniques have been developed for observing these novel states [7,8,9,10,11,12,13], none of them has been able to make a clear distinction between MVSs and GVSs. In this Letter, we present the first experimental evidence for the existence of GVSs and MVSs in a circular disk, and demonstrate magnetic-field induced MVS-GVS and MVS-MVS transitions.…”
mentioning
confidence: 99%
“…Finally, we want to remark that our method can be applied to other geometries such as squares and triangles, in which antivortices might be stabilized for some vorticities [11,12,23,24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, Abrikosov lattice is the most stable configuration of voltices with repulsive force interaction to each other. However, when the system size is small, shape of superconductors, such as boundary condition, affects penetration and arrangement of vortices [1]. Similarly, topology of systems has a potential of affecting the superconducting properties.…”
mentioning
confidence: 99%